2017
DOI: 10.4103/jnacc-jnacc-18.17
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative complications in patients undergoing anterior cervical discectomy and fusion: A retrospective review

Abstract: Background: Anterior cervical discectomy and fusion (ACDF) is a surgical procedure used to manage various cervical spine disorders including spondylosis, prolapsed intervertebral disc, trauma and degenerative disc disease. However, this procedure may be associated with significant post-operative complications. In this study, we aimed to analyse the prevalence of post-operative complications following ACDF. Methods: Perioperative data of 128 patients who underwent ACDF surgery at our institute over a 3-year per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 12 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…In a prospective study, Lee et al found that female revision surgery and multi-level surgery were associated with a higher rate of dysphasia [8]. Yadav et al found that dysphagia was the most common post-operative complaint (16.4%) followed by neurological deterioration (7.9%); one patient suffered from subcutaneous emphysema and hemoptysis due to pharyngeal perforation [14].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, Lee et al found that female revision surgery and multi-level surgery were associated with a higher rate of dysphasia [8]. Yadav et al found that dysphagia was the most common post-operative complaint (16.4%) followed by neurological deterioration (7.9%); one patient suffered from subcutaneous emphysema and hemoptysis due to pharyngeal perforation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cervical discectomy and fusion (ACDF) represents one of the most frequently conducted spinal procedures. ACDF is a widely-used procedure to treat several cervical spine pathologies, such as prolapsed intervertebral disc spondylosis, degenerative disc disease and trauma [ 1 ]. ACDF is in general associated with optimistic clinical outcomes and the majority of patients demonstrate a substantial reduction in neck pain; nevertheless, this procedure may lead to post-operative complications.…”
Section: Introductionmentioning
confidence: 99%
“…Injuries and lesions of the cervical spine are not uncommon 1 . The anterior cervical midline (ACM) approach is a commonly utilised technique in patients with underlying degenerative disc disease, cervical radiculopathy, and cervical myelopathy 2 . The anterior approach can also be utilised in more complex cases, such as cases of tumour resection and ossification of the posterior longitudinal ligament, or in cases where a posterior approach is not optimal, such as cases of existing kyphosis 3‐5 …”
Section: Introductionmentioning
confidence: 99%
“…This could be caused by intubation or direct surgical trauma intraoperatively. Yadav 2 analysed postoperative complications following anterior cervical discectomy and fusion (ACDF) and found that one patient (1/128, 0.78%) suffered pharyngeal perforation and presented postoperatively with subcutaneous emphysema and haemoptysis.…”
Section: Introductionmentioning
confidence: 99%